Analysis of a wall cooling system using a heat pump. (January 2016) - Akbulut, Ugur; Kıncay, Olcay; Utlu, Zafer
Abstract: In this study, a vertical ground source heat pump wall cooling system that belongs to the Yıldız Renewable Energy House at the Davutpaşa Campus of Yıldız Technical University was studied both experimentally and theoretically. The principal objective was to perform a system analysis to determine the parameters that allow the energy usage of the cooling system to be as low as possible. For this reason, a system working in a low temperature regime was chosen. The examination includes energy and exergy analyses conducted during the period between 1 July and 30 September 2012, which is described as the "Summer Session". By using the data that were collected on a per-second basis during these processes and conveyed to a MySQL database, "The moments when the heat pump is activated" were detected, and the "Monthly Average Values" were analyzed. Thus, a theoretical analysis was conducted for the Cooling Session and its correlations. These correlations were used in the energy and exergy analyses. According to the analysis results, the energy and exergy efficiencies of the entire system were found to be 74.85% and 29.90%, respectively, and the Wall Heating Cooling System panels calculated the heat with energy and exergy efficiencies of 90.29% and 80.4%, respectively. Highlights: Vertical type of ground source heat pump wall cooling system working have been studied experimentally and theoretically. Analyses were done by using real data obtained from a prototype structure. Energy and exergy efficiency of all system are 74.85% and 29.90%. Energy and exergy efficiency of WHCS Panels are 90.29% and 80.4%, .